ANALISIS PEMERATAAN PENDAPATAN ANTAR WILAYAH KECAMATAN DI KABUPATEN SEMARANG - Nanang Yusroni; Umar Chadhiq (AKSES: Jurnal Ekonomi dan Bisnis, 2008)
Regional development in Semarang Regent as integral part of national development,  was held for human development, which directed to regional economic development with priority and  potency adjustment. In Semarang regent there was high discrepancy , near to 1 or average 0,66.  It  meant passing of  critical number 0,5.From sector number based on LQ value, the leading sectors on  Semarang  Regent were : industry,  electric power,  gas and water, trade, hotel and restaurant, distribution and communication, and service. With harmony of regional and sector approach which was implemented on development policy, could  give real result in economic growth  trigger and product domestic regional  brutto each of district, utility on economic potency  Key words : Product domestic regional brutto, LQ index. Economic growth